Forgotten Stories of Women: Intergenerational Transmission of Trauma of Holodomor and Holocaust Survivors’ Offspring - Zasiekina, Larysa; Leshem, Becky; Hordovska, Tetiana; Leshem, Neta; Pat-Horenczyk, Ruth (Lesya Ukrainka Volyn National University, 2021)
The aims of this study were to examine the intergenerational effects of two cultural contexts of massive genocide, the Holodomor 1932-1933 in Ukraine, and the Holocaust 1939-1944, on the second and third generations of women in Ukraine and Israel. Forty women participants were recruited for four focus groups, two in each country, comprised of 10 participants each, using a snowball method in both countries. The second generation groups were termed “the mothers’ group”, and the third generation group (comprised of daughters of the mothers’ groups) were called “the daughters’ group”. Inclusion criteria for sampling were (a) being female over 18 years old, and (b) having a family experience of the Famine 1932-1933 / Holocaust, 1939-1944. The groups were moderated by two experienced psychologists in each of the countries. The participants were presented with seven semi-structured questions and were asked to share their family narratives and experiences of the genocide. The study applied inductive thematic analyses that progressed from description to interpretation, for key themes that emerged during the group sessions. The results of the study showed the centrality of five emerging themes in both mothers’ and daughters’ narratives, including “emotions and feelings of experiencing genocide, “attitudes toward food and starvation”, “sense of loss and death”, “transgenerational transmission of trauma in family narratives”, and “ethnic identity”. The cross-cultural perspective of the current research shed light on the similarities and differences between the traumatic narratives constructed by the offspring of the second and the third generations in the two contexts of Ukraine and Israel. The Ukrainian women attributed greater importance of commemoration of Holodomor victims as part of an effective coping with trauma strategy, while the Israeli women put more emphasis on the adoption of asceticism that was inherited from the Holocaust survivors. The cross-cultural clinical and educational implications are discussed.
Keywords: female offspring of Holodomor / Holocaust survivors; mothers-daughters’ narratives; psychotrauma of genocide; transgenerational transmission of trauma